(untitled) (Research, Society and Development, 2024)
Tricyclic antidepressants (TCAs) are a class of psychotropic medications primarily used in the treatment of major depressive disorders, although their indications extend to a variety of psychiatric and neurological conditions. This class of medications was one of the first to be developed for the treatment of depression, marking a revolution in the management of this condition in the mid-20th century. The aim of this study is to present a narrative review in the form of an update on the pharmacokinetic properties, pharmacodynamics, indications, and side effects of tricyclic antidepressants. For this purpose, a narrative review in the format of an update was carried out, which analyzed 42 manuscripts. TCAs have various pharmacological and therapeutic properties, low cost, but their major limitation is their side effects. Since the clinical trials for this class were conducted well before the launch of new antidepressants, new research is needed to allow comparison of these groups within the same methodology and with more up-to-date statistics.